Analysis of analysis: Using machine learning to evaluate the importance of music parameters for Schenkerian analysis. Issue 2 (3rd May 2016) - Kirlin, Phillip B.; Yust, Jason
Abstract : While criteria for Schenkerian analysis have been much discussed, such discussions have generally not been informed by data. Kirlin [Kirlin, Phillip B., 2014 "A Probabilistic Model of Hierarchical Music Analysis." Ph.D. thesis, University of Massachusetts Amherst] has begun to fill this vacuum with a corpus of textbook Schenkerian analyses encoded using data structures suggested byYust [Yust, Jason, 2006 "Formal Models of Prolongation." Ph.D. thesis, University of Washington] and a machine learning algorithm based on this dataset that can produce analyses with a reasonable degree of accuracy. In this work, we examine what musical features (scale degree, harmony, metrical weight) are most significant in the performance of Kirlin's algorithm.